2019
DOI: 10.3168/jds.2018-16033
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effect of Lactobacillus plantarum KSFY02 isolated from naturally fermented yogurt from Xinjiang, China, on d-galactose–induced oxidative aging in mice

Abstract: Yogurt from Xinjiang, China, is a traditional and naturally fermented food, and abundant microorganisms are produced during its fermentation process. In this study, we carried out in vivo animal experiments to explore the effect of a newly isolated lactic acid bacterial strain, Lactobacillus plantarum KSFY02 (LP-KSFY02), on oxidative aging. We used d-galactose to induce oxidative aging in mice and analyzed the serum and tissues of those mice using molecular biology detection methods. The results showed that LP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 38 publications
2
27
0
1
Order By: Relevance
“…The 1 cm 2 sample of skin, liver, and spleen of each mouse was immediately fixed in 10% neutral formalin fixative for 48 hr for histopathological analysis, after H&E staining (hamatoxylin and eosin stain) (Cardiff, Miller, & Munn, 2014), histopathological observation, microscopic examination, and image acquisition and analysis (Zhao et al, 2019).…”
Section: Pathological Observation Of Skin Liver and Spleen Tissuesmentioning
confidence: 99%
“…The 1 cm 2 sample of skin, liver, and spleen of each mouse was immediately fixed in 10% neutral formalin fixative for 48 hr for histopathological analysis, after H&E staining (hamatoxylin and eosin stain) (Cardiff, Miller, & Munn, 2014), histopathological observation, microscopic examination, and image acquisition and analysis (Zhao et al, 2019).…”
Section: Pathological Observation Of Skin Liver and Spleen Tissuesmentioning
confidence: 99%
“…Interest in genus Lactobacilli in particular has grown exponentially in recent decades [ 15 , 16 ]. Studies have demonstrated putative beneficial effects of Lactobacilli probiotics in fields ranging from gastrointestinal to immunological disorders and obesity [ 17 , 18 , 19 , 20 , 21 ]. With regards to bone health, L. casei and L. acidophilus, as probiotic supplements, were fed to ovariectomized (OVX) mice, which are a well-established model used to simulate the estrogen drop-off condition in postmenopausal women [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the last century, biotechnological processes focused on the utilization of pure cultures whereas in the natural environment mostly microbial consortia with complex interactions between the organisms occur (Bader, Mast‐Gerlach, Popović, Bajpai, & Stahl, ). Often traditional fermented foods or beverages were produced by natural microbial consortia, which are abundant in the environment (Bayili et al, ; Somashekaraiah, Shruthi, Deepthi, & Sreenivasa, ; Zhao et al, ). Interactions between different microorganisms were described for many decades (Challinor & Rose, ).…”
Section: Introductionmentioning
confidence: 99%